Function of atypical mammalian oocyte/zygote nucleoli and its implications for reproductive biology and medicine - Fulka, Josef Jr; Benc, Michal; Loi, Pasqualino; Langerova, Alena; Fulka, Helena (The International journal of developmental biology, 2019)
Mammalian oocytes/zygotes contain atypical nucleoli that are composed exclusively of a dense fibrillar material. It has been commonly accepted that these nucleoli serve as a repository of components that are used later on, as the embryo develops, for the construction of typical tripartite nucleoli. Indeed, when nucleoli were removed from immature oocytes (enucleolation) and these oocytes were then matured, fertilized or parthenogenetically activated, development of the produced embryos ceased after one or two cleavages with no detectable nucleoli in nuclei. This indicated that zygotic nucleoli originate exclusively from oocytes, i.e. are maternally inherited. Recently published results, however, do not support this developmental biology dogma and demonstrate that maternal nucleoli in one-cell stage embryos are necessary only during a very short time period after fertilization when they serve as a major heterochromatin organizing structures. Nevertheless, it still remains to be determined, which other functions/roles the atypical oocyte/zygote nucleoli eventually have.
Keywords: maternální dědičnost; embryo savčí; nukleoplasminy; oocyty; Fertilization; Cell Nucleolus; Embryonic Development; zygota; heterochromatin; Embryo, Mammalian; Maternal Inheritance; Nucleoplasmins; Time Factors; Animals; lidé; ženské pohlaví; Heterochromatin; Humans; zvířata; časové faktory; embryonální vývoj; myši; Zygote; Mice; Female; buněčné jadérko; fertilizace; Oocytes